Assessing the economy‐wide impact of food fraud: A SAM‐based counterfactual approach. Issue 2 (7th January 2020) - Rocchi, Benedetto; Romano, Donato; Sadiddin, Ahmad; Stefani, Gianluca
Abstract: This paper proposes a social accounting matrix (SAM)‐based, counterfactual approach to assess the economy‐wide impact of food fraud in a given country and applies it to the Italian economy. The empirical application uses primary data collected by the authority in charge of the monitoring and repression of fraud in food value chains between the years 2007 and 2015. This is a unique dataset to analyze the issue, although it includes only data on food fraud within the country. The results of the SAM simulations show that the share of economy directly and indirectly linked to the supply of irregular food products accounts for 0.5% of the total value of output and is able to activate up to 156 thousand labor units. The net impact of food fraud on output and employment in the whole economy is negative, with losses averaging up to 1.8 billion euros of output and of 20, 000 jobs per year, with a relative impact significantly larger in agriculture than in the food industry. These figures reveal an intrinsic fragility of the agri‐food system, especially in those subsectors featuring relatively large price elasticities such as quality products (e.g., wine, olive oil, cheese). The overall conclusion is that food fraud is not only a source of unfair competition to regular production activities but also has an overall contractionary impact on the whole economy due to its directly unproductive rent‐seeking nature. [EconLit classifications: C67, L66, Q13].